HUBUNGAN PEMBERIAN PENGUATAN VERBAL TERHADAP MOTIVASI BELAJAR SISWA KELAS TINGGI SD INPRES 12/79 BAREBBO - Nur Rizka Mu’ayanah; Makmur Nurdin; Achmad Shabir; Sudarto Sudarto (Bajang Institute, 2022)
This research is a quantitative research with a correlational type of research which aims to determine the description of providing verbal reinforcement in the high class of SD Inpres 12/79 Barebbo, Barebbo District, Bone Regency, to find out the description of the learning motivation of high-class students of SD Inpres 12/79 Barebbo, Barebbo District, Bone Regency, and determine whether there is a significant relationship between the provision of verbal reinforcement on the learning motivation of high-class students in SD Inpres 12/79 Barebbo, Barebbo District, Bone Regency. Variable X in this study is the provision of verbal reinforcement, while variable Y is learning motivation. The population in this study were all highgrade students of SD Inpres 12/79 Barebbo, Barebbo District, Bone Regency, totaling 50 students. The sampling technique in this study used non-probability sampling technique. Research data obtained by collecting data through a questionnaire. The data analysis technique used descriptive statistical analysis and inferential statistical analysis. The results of descriptive statistical analysis showed that the provision of verbal reinforcement was classified as moderate with a percentage of 60% and student learning motivation was classified as moderate with a percentage of 70%. The results of inferential statistics show that the correlation coefficient (rcount) is greater (≥) value (rtable), namely 0.411 0.278 and sig 0.003 0.05 (significance level 5%) so that H0 is rejected and H1 is accepted. From the results of the study, it can be concluded that there is a significant relationship between the provision of verbal reinforcement on the learning motivation of high-class students at SD Inpres 12/79 Barebbo, Barebbo District, Bone Regency.